The Transformation from Translucent into Transparent Rare Earth Ions Doped Oxyfluoride Glass‐Ceramics with Enhanced Luminescence. Issue 13 (11th May 2022) - Li, Zhencai; Chen, Chunying; Shen, Weihui; Zhou, Dacheng; Jensen, Lars R.; Qiao, Xvsheng; Ren, Jinjun; Du, Jincheng; Zhang, Yanfei; Qiu, Jianbei; Yue, Yuanzheng
Abstract: It is known that the optical transparency of an oxide glass decreases with an increase in the size and fraction of crystals in the glass during heat‐treatment. Here, the authors report an opposite scenario, where a translucent Er 3+ −Yb 3+ doped oxyfluoride precursor glass‐ceramic (P‐GC) becomes transparent with increasing crystal size and crystallinity. Specifically, in the heat‐treated P‐GC samples, the authors observe that the growth of the existing Ba2 LaF7 crystals and particularly the formation of small spherical Ba2 LaF7 crystals greatly enhanced the light transmittance. To reveal the origin of this anomalous phenomenon, the authors perform detailed morphology and structure analyses on both P‐GC and the heat‐treated P‐GC samples and molecular dynamics simulations of the precursor glass. The results show that the composition of the residual glass phase is altered (e.g., depletion of La 3+ ) in the way that the differences in refractive index between the glass matrix and the crystals are greatly reduced. As a consequence, the light scattering of the heat‐treated P‐GC is suppressed, and hence, the derived P‐GC becomes transparent. In addition, a proper heat‐treatment can also enhance the luminescence of the studied P‐GC system. Abstract : A new type of translucent Er 3+ −Yb 3+ doped oxyfluoride precursor glass‐ceramic (P‐GC) containing large flower‐like Ba2 LaF7 single‐crystals is prepared via melt‐quenching. The translucent oxyfluoride P‐GC becomes transparent with increasing the crystal size and crystallinity as a result of isothermal heat‐treatment. This is attributed to the suppression of light scattering. The derived transparent P‐GC shows strong up‐conversion luminescence.